Involvement of the proteasome in the programmed cell death of NGF-deprived sympathetic neurons. - Sadoul, R (1996)
Sympathetic neurons undergo programmed cell death (PCD) upon deprivation of nerve growth factor (NGF). PCD of neurons is blocked by inhibitors of the interleukin-1beta converting enzyme (ICE)/Ced-3-like cysteine protease, indicating involvement of this class of proteases in the cell death programme. Here we demonstrate that the proteolytic activities of the proteasome are also essential in PCD of neurons. Nanomolar concentrations of several proteasome inhibitors, including the highly selective inhibitor lactacystin, not only prolonged survival of NGF-deprived neurons but also prevented processing of poly(ADP-ribose) polymerase which is known to be cleaved by an ICE/Ced-3 family member during PCD. These results demonstrate that the proteasome is a key regulator of neuronal PCD and that, within this process, it is involved upstream of proteases of the ICE/Ced-3 family. This order of events was confirmed in macrophages where lactacystin inhibited the proteolytic activation of precursor ICE and the subsequent generation of active interleukin-1beta.